Clinical correlations of mutations affecting six components of the SWI/SNF complex: Detailed description of 21 patients and a review of the literature. Issue 6 (1st May 2013) - Kosho, Tomoki; Okamoto, Nobuhiko; Ohashi, Hirofumi; Tsurusaki, Yoshinori; Imai, Yoko; Hibi‐Ko, Yumiko; Kawame, Hiroshi; Homma, Tomomi; Tanabe, Saori; Kato, Mitsuhiro; Hiraki, Yoko; Yamagata, Takanori; et al.
Abstract Mutations in the components of the SWItch/sucrose nonfermentable (SWI/SNF)‐like chromatin remodeling complex have recently been reported to cause Coffin–Siris syndrome (CSS), Nicolaides–Baraitser syndrome (NCBRS), and ARID1B‐related intellectual disability (ID) syndrome. We detail here the genotype‐phenotype correlations for 85 previously published and one additional patient with mutations in the SWI/SNF complex: four with SMARCB1 mutations, seven with SMARCA4 mutations, 37 with SMARCA2 mutations, one with an SMARCE1 mutation, three with ARID1A mutations, and 33 with ARID1B mutations. The mutations were associated with syndromic ID and speech impairment (severe/profound in SMARCB1, SMARCE1, and ARID1A mutations; variable in SMARCA4, SMARCA2, and ARID1B mutations), which was frequently accompanied by agenesis or hypoplasia of the corpus callosum. SMARCB1 mutations caused "classical" CSS with typical facial "coarseness" and significant digital/nail hypoplasia. SMARCA4 mutations caused CSS without typical facial coarseness and with significant digital/nail hypoplasia. SMARCA2 mutations caused NCBRS, typically with short stature, sparse hair, a thin vermillion of the upper lip, an everted lower lip and prominent finger joints. A SMARCE1 mutation caused CSS without typical facial coarseness and with significant digital/nail hypoplasia. ARID1A mutations caused the most severe CSS with severe physical complications. ARID1B mutations caused CSS without typical facial coarseness and with mild digital/nail hypoplasia, or caused syndromic ID. Because of the common underlying mechanism and overlapping clinical features, we propose that these conditions be referred to collectively as "SWI/SNF‐related ID syndromes". © 2013 Wiley Periodicals, Inc.